Case Report: Mild and complete thyroid peroxidase deficiency in a family with literature review - Wu, Xiaobi; Yan, Yuerong; Wu, Hongshi; Woo, Kwan Leong; Wu, Muchao; Yan, Li; Li, Yan; Zhang, Jin (Frontiers in Medicine, 2025)
Mild thyroid peroxidase (TPO) deficiency is an extremely rare autosomal recessive genetic disorder, with fewer than 10 cases reported globally. This condition is often misdiagnosed as primary hypothyroidism. We report a family with mild and complete TPO deficiency due to TPO gene mutations, including a novel mutation (p.R584W; c.1750 T > G). The literature was reviewed to provide references for early clinical diagnosis and treatment. The proband was a 27-year-old man with a 20-year history of goiter and abnormal thyroid function. Thyroid function tests showed decreased thyroxine and free thyroxine levels, increased triiodothyronine and free triiodothyronine levels, elevated FT3/FT4 ratios, normal thyroid stimulating hormone levels, and elevated thyroglobulin levels. Ultrasound highlighted goiter with multiple nodules. Previous treatment with levothyroxine (L-T4) showed no improvement in goiter nor thyroid function, leading to discontinuation. Genetic sequencing revealed a heterozygous TPO gene mutation (p.R584W; c.1750 T > G), predicted to be harmful by software including REVEL, PolyPhen2, and MutationTaster (REVEL score: 0.959). The proband’s brother carried the same mutation albeit with different clinical manifestations, diagnosed as complete TPO deficiency. Moreover, the clinical characteristics and gene mutations of the nine previously reported cases of mild TPO deficiency were reviewed and summarized. Hence, this study reported a family with mild and complete TPO deficiency due to TPO gene mutations, and the literature was reviewed to enhance clinicians’ understanding of the disease. Gene mutations aid in diagnosis. This is the first study to report the p.R584W; c.1750 T > G gene mutation, enriching the gene pool for this rare disease. The efficacy of L-T4 treatment for mild TPO deficiency requires further observation and research.